Analysis Of The Synergy Development Of The Creative Economy And Tourism Sector Of East Sumba Regency - Fransina Welhelmina Ballo; Maria Indriyani Hewe Tiwu (Green Publisher Indonesia, 2021)
This study aims to analyze the strategy for developing a synergy between the creative economy and the tourism sector in East Sumba Regency. What is the right strategy for developing synergy between the creative economy and the tourism sector in East Sumba Regency. This area has a variety of tourism objects, both natural, marine, and cultural tourism. The development of the tourism sector supports changes in the lives of the surrounding community, especially those around tourist attractions, especially with regard to income. The method used in this study is a mix method. From the results of the analysis it was found that the tourism sector in East Sumba Regency is not supported by the creative economy so that the tourism sector has not become a locomotive for the regional economy. So the right strategy is that the East Sumba regency government must build concrete cooperation between local governments, communities, traditional leaders, academics and the mass media. In addition, to build economic independence in each region or region, especially in East Sumba Regency, it is necessary to create a synergy between the tourism sector and the creative economy or creative industry that can encourage the creation of new economic sources and the opening of new jobs, so that the national development goals of a prosperous society can be achieved.